MYCOBACTERIUM AVIUM SUBSP. PARATUBERCULOSIS IN DAIRY CATTLE IN THE LIMA AREA DETECTED THROUGH THREE DIAGNOSTIC TECHNIQUES - Bustamante V., José (2011)
The objective of the study was to determine the presence of Mycobacterium avium subsp. paratuberculosis (Map) in dairy cattle in Lima, Peru. The Intradermal Tuberculin Test was applied to 60 cows from three herds and serum samples were tested using two commercial ELISA kits for antibodies against Map. Twenty-two cows (36.7%) were positive to at least to one of these diagnostic techniques (8 to one of the ELISA tests and 18 to the intradermal test). Feacal samples from the 22 positive animals were cultured on Herrold’s egg-yolk medium (HEYM) yielding five Map positive samples. PCR was used in the isolated strains and Map DNA was confirmed in two cows. A slight concordance (0.15, Kappa test) was found between techniques evaluating cellular and humoral immune response, establishing that these tests are not interchangeable (5.55> 3.84, Mc Nemar test). The results confirm the presence of Map in dairy cattle in Lima, Peru.